PEMBERDAYAAN PENYANDANG DISABILITAS MELALUIPROGRAM KETRAMPILAN HANDYCRAFT UNTUKMENDORONG KEMANDIRIAN EKONOMIDI PAGUYUPAN DISABILITAS KRIDA KARYA MANDIRI - Faujianto, Samsu Anhari; Rohmatiah, Ahadiati; Iswati, Retno; Lukito, Martin (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. This community service program aims to improve performance at the production, management, and product marketing stages independently and sustainably. The method used is through dissemination and counseling on product ideas by looking at market demand conditions but also taking into account the capabilities of existing resources. The development of productive economic activities needs to be carried out by developing various types of market-oriented business skills. Through identifying the potential and resources of the participants, both human, institutional, financial, and facilities and infrastructure that can be utilized, then training by utilizing e-commerce for product marketing and providing assistance in implementing skills guidance, as well as developing productive economic activities are carried out by developing various types of business skills that are economically valuable and market-oriented. After providing assistance and knowledge transfer, there were several positive impacts, including a change in the mindset of persons with disabilities to be more empowered and independent by exploring their potential, product opportunities were more widely explored, to increase branding, thereby increasing income, and diversity of livelihoods that can be an alternative for the community to carry out their lives. In the end, the community service activities felt by the Krida Karya Mandiri Association were that participants were able to make and sell useful, interesting, and artistic crafts by utilizing technological developments. In the economic field, persons with disabilities are empowered through the utilization of natural potential and human resources. And in the social field, empowered to always be optimistic and independent. Abstrak. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatan kinerja di tahap produksi, manajemen, hingga pemasaran produk secara mandiri dan keberlanjutan. Metode yang digunakan melalui sosialisasi dan penyuluhan gagasan produk dengan melihat kondisi permintaan pasar namun juga memperhatikan kemampuan sumber daya yang ada. Pengembangan kegiatan ekonomi produktif perlu dilaksanakan dengan mengembangkan berbagai jenis ketrampilan usaha yang berorientasi pada pasar. Melalui identifikasi potensi dan sumber daya peserta baik sumber daya manusia, kelembagan, finansial maupun sarana dan prasarana yang dapat dimanfaatkan, kemudian pelatihan dengan memanfaatkan e-commerce untuk pemasaran produk dan melakukan pendampingan dalam pelaksanaan bimbingan ketrampilan, serta pengembangan kegiatan ekonomi produktif dilaksanakan dengan mengembangkan berbagai jenis ketrampilan usaha yang bernilai ekonomis dan berorientasi pada pasar. Setelah melakukan pendampingan dan transfer ilmu pengetahuan, terdapat beberapa dampak positif antara lain adanya perubahan mindset dari penyandang disabilitas untuk lebih berdaya dan mandiri dengan menggali potensi yang dimilikinya, peluang produk lebih tereksplor secara luas, sehingga dapat meningkatkan branding, dengan begitu akan meningkatkan pendapatan, serta keragaman mata pencaharian yang dapat menjadi alternatif masyarakat untuk melangsungkan kehidupannya. Pada akhirnya, kegiatan pengabdian masyarakat yang dirasakan oleh Paguyupan Disabilitas Krida Karya Mandiri adalah peserta telah mampu membuat dan menjual kerajinan yang bermanfat, menarik dan memiliki nilai seni dengan memanfaatkan perkembangan teknologi. Dalam bidang ekonomi, penyandang disabilitas diberdayakan melalui pemanfaatan potensi alam maupun sumber daya manusia. Dan dalam bidang sosial, diberdayakan untuk selalu bersikap optimis dan mandiri.